Mitochondrial gene heterogeneity of the bat soft tick Argas vespertilionis (Ixodida: Argasidae) in the Palaearctic - Hornok, Sándor; Szőke, Krisztina; Tu, Vuong Tan; Kontschán, Jenő; Takács, Nóra; Sándor, Attila D.; Halajian, Ali; Földvári, Gábor; Estók, Péter; Plantard, Olivier; Epis, Sara; Görföl, Tamás (Parasites & Vectors, 2017)
Background: Recently, a high degree of mitochondrial gene heterogeneity was demonstrated between conspecific ixodid ticks of bats in Eurasia. Argas vespertilionis is a soft tick species of mainly vespertilionid bats, also with a wide distribution in the Old World. The aim of this study was to investigate the morphology, mitochondrial gene heterogeneity and host range of A. vespertilionis in the Old World. Results: Altogether 318 soft tick larvae were collected from 17 bat species (belonging to six genera) in seven countries. Based on the general morphology (setal arrangement) of 314 A. vespertilionis larvae, and the detailed measurements of fifteen larvae, only minor morphological differences (in dorsal plate size and the type of serrate setae) were observed between specimens from Europe and Vietnam. On the other hand, cytochrome c oxidase subunit 1 (cox1) and 16S rRNA gene sequence analyses of 17 specimens showed that A. vespertilionis from Europe is genetically different (with up to 7.5% cox1 and 5.7% 16S rRNA gene sequence divergence) from specimens collected in Vietnam, and their phylogenetic separation is well supported. Conclusion: In its evaluated geographical range, no larval phenotypic differences justify the existence of separate species under the name A. vespertilionis. However, phylogenetic analyses based on two mitochondrial markers suggest that it represents a complex of at least two putative cryptic species. The broad host range of A. vespertilionis might partly explain its lower degree of mitochondrial gene heterogeneity in comparison with ixodid bat tick species over the same geographical region of Eurasia.
Journal article published in the journal of Parasites & Vectors (2017) 10:109
Keywords: Soft tick; Chiroptera; Phylogeny; Phylogeography; Cryptic species; Argasidae; Bats; Mitochondrial DNA